THE ROLE OF THE SELLING AND DISPLAY PROCESS TO INCREASE P&G PRODUCT SALES IN THE GUNUNG SARI MARKET, WEST LOMBOK - Wawan Setyawan; Melinda Christanti Kwan (Penelitian dan Pengembangan Ilmu, 2025)
In the supply chain of a product to reach consumers, a significant role is needed from the distributor. Sales performance and achieving maximum distribution are the main goals that must continue to be achieved. However, the challenges of tight competition between competitors make achieving these goals not easy. The ability to strategize, execute, evaluate, and continuously innovate is one of the keys to the success of a distributor. The decline in sales that occurred in P&G products in Gunung Sari Market is part of a phenomenon that occurs in a supply chain that is run. The research conducted is an effort to increase sales again by using a qualitative descriptive method that prioritizes detailed descriptions based on empirical data collected from the field. By taking the object of research, namely the sale of P&G products in Gunung Sari Market, Lombok . Based on the results obtained, there is a very close relationship between the selling and display processes in increasing sales of P&G products at the Gunung Sari Market, West Lombok. The impact of the increase in sales that occurs can be used as a reference for carrying out the same pattern and implementing it in other areas within the company.